Differences in Students’ Interest in Physics by Gender and Stage of Schooling in Kerala - K. A bdul G afoor (JOURNAL OF INDIAN EDUCATION, 2013)
Amid worldwide studies indicating declining students’ interest in physics during secondary stage especially among girls, this study explores boys’ and girls’ interest in physics and changes thereof as students go up the educational ladder, on a sample of 1509 boys and 1727 girls in upper primary to higher secondary schools in Kerala. It employed a combination of cross-sectional and longitudinal designs of survey. Interest in physics was measured as sum of preference scores on a set of physics topics at upper primary, high school and higher secondary stages. Irrespective of gender, interest in physics topics is highest at the upper primary stage, with a slight advantage for girls. In general, by high school, there is 12% decline in interest in physics and a further 14% decline by higher secondary stage; decline being more among girls than boys. Decline in interest of girls is more in physics than interest in science in general; decline in interest of boys is less in physics than interest in science in general. The findings are discussed in view of self-related knowledge of students, achievement and instructional practices.